HUMAN CAPITAL AND ORGANIZATIONAL CLIMATE ON THE PERFORMANCE OF ONLINE MEDIA INDUSTRY EMPLOYEES - Mustapa, Zainuddin (Journal of Entrepreneur, Business and Management, 2024)
This research aims to explore, analyze, and interpret the impact of Human Capital and Organizational Climate on the performance of Online Media Industry Employees in Makassar. The research approach used is quantitative descriptive, with a population and sample consisting of 32 employees. Data collection is conducted through interviews, questionnaires, and literature review. The obtained data will be analyzed using statistical tools and SPSS software version 24. The research results indicate that: 1. Human Capital has a positive and significant impact on the performance of Online Media Industry Employees in Makassar. Overall, Human Capital has a strong influence in enhancing employee performance, which is a crucial factor in achieving organizational goals. 2. Organizational Climate also has a positive and significant impact on the performance of Online Media Industry Employees. Organizational Climate is an important factor that supports employees in developing their potential optimally to support organizational goals with full awareness.